LEGAL PROTECTION OF BANK INDONESIA’S FINANCIAL INDEPENDENCE - Deviana, Ayu (Bank Indonesia, 2024)
Bank Indonesia as the central bank in Indonesia has financial independence in which Bank Indonesia has the authority to manage its assets separately from the State Budget. However, in carrying out its roles and duties, Bank Indonesia often faces demands or lawsuits, which result in execution of judgments against assets of Bank Indonesia. This can clearly disrupt the financial stability of Bank Indonesia, affecting Bank Indonesia’s ability to carry out its roles and duties effectively. Currently, there has been an argument put forth to assert Article 50 of the treasure law in an effort to protect for Bank Indonesia’s finances. However, the application of this article as a legal basis for protection of Bank Indonesia’s finances is inappropriate because it is not in accordance with Bank Indonesia’s financial independence, separating from the State Budget. Departing from these problems, based on data collected through document studies in the form of primary, secondary, and tertiary legal materials, this study examines how the policies of financial independence of Bank Indonesia, legal protection of Bank Indonesia’s finance, and ideal arrangements for legal protection of Bank Indonesia’s finances considering the attention to the independence of Bank Indonesia. The conclusion of this research is that there is still disharmony in regulations regarding Bank Indonesia’s financial protection in the State Finances Law and the State Treasury Law which creates legal uncertainty regarding Bank Indonesia’s financial protection.